Setting course for sustainability : evaluating resident‘s perspectives of cruise tourism in Ísafjörður, Iceland - Elizabeth Riendeau 1998- (2023)
The steep growth of cruise ship tourism worldwide has led to concerns about how destinations are able to cope with the increasing volume of tourists. Cruise tourism is associated with several social, and environmental impacts that can often call into question the industry’s sustainability. This study focuses on Ísafjörður, a small town situated in the Westfjords of Iceland with a rapidly increasing cruise tourism influx. Following up on a previous study of the social sustainability of cruise calls to Ísafjörður from 2013 (O’Brien, 2014), this thesis explores changes in the perspective of residents towards cruise passengers over a decade. Since then, other studies were conducted on the topic, however, none were conducted utilizing a community survey, or considering post-COVID-19 tourism. I seek to identify how much cruise ship tourism is wanted by residents and their attitudes and tolerance of the industry. Furthermore, this thesis explores the perspectives of managing stakeholders and experts to understand how they might contrast with those of residents. A community survey was used to gauge the resident's tolerance, while interviews were conducted with five key stakeholders. Results show that the cruise industry in Ísafjörður has reached its carrying capacity, and residents are against further growth. However, support for the status quo was found to be more divided, with many residents found to be tolerant towards the current number of incoming tourists. Based on these findings, it is recommended to put in place a cap on cruise passenger numbers, while ensuring that new limitations are informed by local voices. Skörp aukning skemmtiferðaskipa þjónustu um allan heim hefur valdið áhyggjum um hvernig viðkomustaðir geti glímt við aukið magn ferðamanna. Skemmtiferðaskipa þjónusta tengist þó nokkrum félags, og umhverfisáhrifum sem geta oft vakið spurningar um sjálfbærni starfseminnar. Þessi rannsókn beinist að Ísafirði, litlum bæ á Vestfjörðum með hratt auknu innflæði á skemmtiferðaskipa þjónustu. Með eftirfylgni á ...